2006
DOI: 10.1111/j.1469-8749.2006.tb01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term use of the ketogenic diet in the treatment of epilepsy

Abstract: Long-term outcomes of the ketogenic diet in the treatment of epilepsy have not previously been reported. A retrospective chart review of children treated with the ketogenic diet for more than 6 years at the Johns Hopkins Hospital was performed. The response was documented at clinic visits and by telephone contacts; laboratory studies were obtained approximately every 6 to 12 months. Satisfaction and tolerability were assessed by means of a brief parental telephone questionnaire. In all, 28 patients (15 males, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 19 publications
0
20
0
2
Order By: Relevance
“…After 12 wk, weight gain is similar in both groups of mice. Long-term use of KD in children with epilepsy resulted in slowed growth but did not change the body mass index (17,28,39). In rats it has been shown that 4 -6 wk KD leads to visceral fat accumulation (32) and increased leptin LONG-TERM KETOGENIC DIET REDUCES ␤-AND ␣-CELL MASS concentrations (10).…”
Section: Discussionmentioning
confidence: 99%
“…After 12 wk, weight gain is similar in both groups of mice. Long-term use of KD in children with epilepsy resulted in slowed growth but did not change the body mass index (17,28,39). In rats it has been shown that 4 -6 wk KD leads to visceral fat accumulation (32) and increased leptin LONG-TERM KETOGENIC DIET REDUCES ␤-AND ␣-CELL MASS concentrations (10).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of impaired growth in children on the KD [29,30]; younger children may be more at risk [19]. Long-term follow up of children treated with the KD in the past suggests that although growth does improve after the diet is discontinued, height gain can still be below expected [31].…”
Section: Growthmentioning
confidence: 99%
“…22 Administration of potassium citrate can reduce the risk to .9%. 23 Despite the independent risk for kidney stone development associated with use of carbonic anhydrase inhibitors (eg, topiramate and zonisamide), its concurrent administration with KD does not appear to increase the risk.…”
Section: Kidney Stonesmentioning
confidence: 99%